2015
DOI: 10.1111/jog.12840
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of recurrence and survival after abdominal versus laparoscopic/robotic radical hysterectomy in patients with early cervical cancer

Abstract: Total laparoscopic/robotic intracorporeal colpotomy under CO2 pneumoperitoneum may carry a risk of positive vaginal cuff margin, as well as intraperitoneal tumor spreads in patients with early-stage cervical cancer treated with LRH/RRH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
90
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(105 citation statements)
references
References 30 publications
4
90
1
1
Order By: Relevance
“…Additionally, exposing the tumor to circulating carbon dioxide can lead to loco-regional tumor implants 28. Despite some reservations regarding manipulator application,29 it has been widely used and considered safe among most gynecologic oncologists 6 30. In contrast, our group has established a surgical technique combining a laparoscopic and vaginal approach,14 in which we never used any uterine manipulator and always created a tumor-covering vaginal cuff transvaginally.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, exposing the tumor to circulating carbon dioxide can lead to loco-regional tumor implants 28. Despite some reservations regarding manipulator application,29 it has been widely used and considered safe among most gynecologic oncologists 6 30. In contrast, our group has established a surgical technique combining a laparoscopic and vaginal approach,14 in which we never used any uterine manipulator and always created a tumor-covering vaginal cuff transvaginally.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the introduction, peritoneal dissemination of cervical cancer cells by intracorporal colpotomy may be the main factor for increased recurrence rates in patients treated by laparoscopic radical hysterectomy …”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the introduction, peritoneal dissemination of cervical cancer cells by intracorporal colpotomy may be the main factor for increased recurrence rates in patients treated by laparoscopic radical hysterectomy. 1,8,9,[14][15][16][17][18] Some findings indicate a prognostic role of tumor cell spillage potomy is essential to prevent peritoneal tumor dissemination. [6][7][8] Therefore, a vaginal cuff is formed to cover the cervix completely Other experts criticize the frequent use of uterine manipulators during laparoscopic radical hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports the possible role of peritoneal diffusion of neoplastic cells from the embolization of the tumor and the pneumoperitoneum in minimally invasive surgery. This topic was evaluated by Kong et al13 in a retrospective analysis of 128 patients with FIGO stage IB and IIA cervical cancer, who underwent laparoscopic or robotic radical hysterectomy. Multivariate analysis demonstrated that laparoscopic intra-corporeal colpotomy represented a strong prognostic factor related to disease recurrence (OR=7.04, 95% CI 1.06 to 15.18; p<0.041), with five patients who presented peritoneal recurrence in this group.…”
Section: Discussionmentioning
confidence: 99%